Pemaduan Perencanaan Pembangunan dan Perencanaan Keruangan - Ahyuni, Ahyuni (Fakultas Ilmu Sosial Universitas Negeri Padang, 2011)
ABSTRACT Planning system in Indonesia consists of development planning system and spatial planning system. The first emphasizes on sectoral approach and the second on spatial comprehensive approach. The two systems should be integrated as a basis for developing budget planning and evaluating development performance, but unfortunately it is not carried out fully in practice. Discrepancies of planning timeÂ period, differentiation between focus of planning substances and implementation procedures, and sectoral fragmented planning performance evalution still happened. This paper tries to discuss the integration of the Indonesian planning system and the strategies to solve the problem. Kata Kunci: Sistem perencanaan, perencanaan pembangunan, perencanaan keruangan, keterpaduan perencanaan